The Psychology of Food Cravings in Patients With First-Episode Psychosis - Kim, Young-Hyuk; Ryu, Seunghyong; Nam, Hee-Jung; Kim, Mina; Jhon, Min; Lee, Ju-Yeon; Kim, Jae-Min; Shin, Min Ho; Chung, Young-Chul; Kim, Sung-Wan (Frontiers in Psychiatry, 2020)
Objectives: Food cravings may cause weight gain in patients with schizophrenia. This study investigated psychological characteristics associated with food cravings in patients with first-episode psychosis. Methods: This study analyzed data from a clinical cohort of first-episode psychosis patients taking antipsychotics for 3 months or less. The strength of food cravings was measured using the General Food Cravings Questionnaire-Trait (G-FCQ-T). Psychological characteristics and psychiatric symptoms were investigated with the Positive and Negative Symptom Scale (PANSS), Calgary Depression Scale for Schizophrenia (CDSS), Social and Occupational Functioning Assessment Scale, Rosenberg Self-Esteem Scale (RSES), and Perceived Stress Scale (PSS). Clinical characteristics were compared according to significant weight gain (≥10% increase in body weight compared to baseline) over 3 months. Associations between the G-FCQ-T and other psychiatric scales were investigated. We conducted sex-stratified analyses. Results: In total, 182 patients (78 males and 104 females) with first-episode psychosis were enrolled in this study. In females, the G-FCQ-T total score at baseline was associated with baseline body weight and significant weight gain over 3 months. The PSS scales were significantly associated the G-FCQ-T total and all subscale scores in female participants. Scores on the RSES and CDSS were significantly associated with the G-FCQ-T total score and with the preoccupation and loss of control subscale scores. The PANSS negative and general subscales were significantly associated with the positive outcome expectancy and loss of control subscales of the G-FCQ-T, respectively. In males, the only significant association was between the loss of control subscale and RSES scores. Linear regression analysis showed significant associations of PSS scores with the total and all subscale scores of the G-FCQ-T despite the loss of significance for other variables. Conclusion: These results indicate that the food cravings in patients with first-episode psychosis, which were associated with weight gain, were influenced by perceived stress in females. To reduce food cravings in female patients with schizophrenia, interventions aimed at perceived stress should be considered.